1980
DOI: 10.1212/wnl.30.10.1125
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage with amphetamine abuse

Abstract: Intracranial hemorrhage (ICH) occurred in a drug abuser soon after self-administration of amphetamine. Other reported cases indicate a consistent clinical picture, sometimes fatal or causing permanent neurologic disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(38 citation statements)
references
References 0 publications
1
35
0
2
Order By: Relevance
“…In the literature, amphetamine and MArelated CVAs are predominantly hemorrhagic strokes. 5,[7][8][9][10][11][12] Paradoxically, hemorrhagic strokes account for less than one fourth of CVAs in the general population. 13 MA-related ICHs have been reported in all cerebral lobes, with the majority involving the frontal lobe, as seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, amphetamine and MArelated CVAs are predominantly hemorrhagic strokes. 5,[7][8][9][10][11][12] Paradoxically, hemorrhagic strokes account for less than one fourth of CVAs in the general population. 13 MA-related ICHs have been reported in all cerebral lobes, with the majority involving the frontal lobe, as seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of other detrimental physical and mental health consequences can occur, including nutritional deficiencies, sleep deprivation, and rapid tooth decay, known as "meth mouth" (ADA Division of Communications 2005; National Institute on Drug Abuse 2006). A number of cases of MA-related mortality have been reported, not only due to excessive use or overdosing, but also because of hypersensitivity to MA or the drug's prominent hypertensive effects (e.g., Delaney and Estes 1980;Hall et al 1973). In addition, MA abusers have significantly elevated infection rates for diseases such as human immunodeficiency virus (HIV) and hepatitis C virus (HCV) as a result of both injection drug use (i.e., needle sharing) and risky sexual behavior (e.g., unprotected sex), especially among the population of men who have sex with men (Bluthenthal et al 2001;Gonzales et al 2006;Halkitis et al 2001;Shoptaw 2006).…”
Section: Effects Of Chronic Methamphetamine Usementioning
confidence: 99%
“…Angiographic evidence of spasm has also been seen acutely following the intracisternal injection of norepinephrine.' 3 Although extracerebral angiitis has been well demonstrated in drug abusers, 4 14 few attempts have been made to correlate cerebral arteriographic changes with histopathology. In 16 amphetamine-related haemorrhages reviewed by Delaney and Estes, 3 10 patients underwent angiography and beading was demonstrated in only 4.…”
mentioning
confidence: 99%
“…3 Although extracerebral angiitis has been well demonstrated in drug abusers, 4 14 few attempts have been made to correlate cerebral arteriographic changes with histopathology. In 16 amphetamine-related haemorrhages reviewed by Delaney and Estes, 3 10 patients underwent angiography and beading was demonstrated in only 4. Of these, pathological study was lacking in 3, and necrotizing cerebral angiitis was demonstrated in the remaining patient."…”
mentioning
confidence: 99%